Ineffectiveness of the Dzyaloshinskii–Moriya interaction in the dynamical quantum phase transition in the ITF model. (1st October 2018) - Cheraghi, Hadi; Mahdavifar, Saeed
Abstract: Quantum phase transition occurs at a quantum critical value of a control parameter such as the magnetic field in the Ising model in a transverse magnetic field (ITF). Recently, it is shown that ramping across the quantum critical point generates non-analytic behaviors in the time evolution of a closed quantum system in the thermodynamic limit at zero temperature. The mentioned phenomenon is called the dynamical quantum phase transition (DQPT). Here, we consider the one-dimensional ITF model with added the Dzyaloshinskii–Moriya interaction (DMI). Using the fermionization technique, the Hamiltonian is exactly diagonalized. Although the DMI induces chiral phase in the ground state phase diagram of the model, the study of the rate function of the return probability has proven that the DMI does not affect the DQPT. We conclude accordingly that the ramping across the quantum critical point is not a necessary and sufficient condition for DQPT.